Production and application of monoclonal antibodies to GST - WU Jian-xiang; CHEN Tian-jia; ZHOU Xue-ping (浙江大学学报. 农业与生命科学版)
Two hybridoma cell lines (4B3 and 1H10) secreting monoclonal antibodies (McAbs) against recombinant GST were produced by fusing mouse myeloma cells (SP2/0) with spleen cells from BALB/C immunized by the purified GST protein and subsequently three-time limited dilution method. The titres of ascitic fluids of the two McAbs were up to 10-6 in indirect ELISA. Isotypes and subclasses of 1H10 and 4B3 all belong to IgG1, κ. Western-blot showed that the two McAbs can specifically react with GST-IBV-S1-F and recombinant GST. The McAb 1H10 has successfully been used in immunoaffinity chromatography of GST fusion protein.